Step-by-step explanation:
the total surface area is the sum of the individual areas.
we have the ground area : a 6×6 square. = 36 cm²
and we have 4 equal triangles.
the area of a triangle is baseline × height / 2.
which is for each of these triangles
6 × 12 / 2 = 3 × 12 = 36 cm²
so, the total surface area of the pyramid is
36 + 4×36 = 5×36 = 180 cm²
Answer:
B
Step-by-step explanation:
5x² - 3 - (x² - 4x - 8)
5x² - 3 - x² + 4x + 8
4x² + 4x + 5
I think its d.... but dont listen to me.<span>
</span>
Answer:
Q=(2,-1)
Step-by-step explanation:
We are given point as N=(-1,2)
Point Q is symmetric to point N with respect to line y=x
we know that any point symmetric with respect to line y=x means inverse of that point
For example: If we have to find symmetric about y=x line of point (a,b)
a changes to b
and b changes to a
so, symmetric of (a,b) with respect to y=x line would be (b,a)
We have point N(-1,2)
-1------>2
2----->-1
so, we get point as
Q=(2,-1)